2021
DOI: 10.1038/s41598-021-89189-1
|View full text |Cite
|
Sign up to set email alerts
|

Towards a neutron and X-ray reflectometry environment for the study of solid–liquid interfaces under shear

Abstract: A novel neutron and X-ray reflectometry sample environment is presented for the study of surface-active molecules at solid–liquid interfaces under shear. Neutron reflectometry was successfully used to characterise the iron oxide–dodecane interface at a shear rate of $$7.0\times {}10^{2}$$ 7.0 × 10 2 $$\hbox {s}^{… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…This can be quantified by comparing the natural logarithm of Z for modelling the substrate with (ln Z = 804.8 ± 0.5) and without (ln Z = −177.0 ± 0.5) the adventitious layer, where models with greater Bayesian evidences are preferable. The presence of adventitious material at the iron oxide–dodecane interface has been reported previously, 21 and comparable layers have been found at interfaces between materials of high and low surface energy. 61–64 The details of this model, including the parameterisation of the adventitious layer and the magnetisation of the iron layer, and the subsequent results, are given in the ESI †…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This can be quantified by comparing the natural logarithm of Z for modelling the substrate with (ln Z = 804.8 ± 0.5) and without (ln Z = −177.0 ± 0.5) the adventitious layer, where models with greater Bayesian evidences are preferable. The presence of adventitious material at the iron oxide–dodecane interface has been reported previously, 21 and comparable layers have been found at interfaces between materials of high and low surface energy. 61–64 The details of this model, including the parameterisation of the adventitious layer and the magnetisation of the iron layer, and the subsequent results, are given in the ESI †…”
Section: Resultssupporting
confidence: 82%
“…In recent experimental work, a cell has been developed that allows the interfacial structures of adsorbed films to be studied under shear conditions using either X-ray or neutron reflectometry. 21 In the initial demonstration of the cell, GMO was studied at the interface between n -dodecane and planar iron oxide (hematite, Fe 2 O 3 ) surfaces. It was found that GMO forms a layer approximately 25 Å thick, which does not alter significantly between quiescent and shear conditions (shear rate 700 s −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…n -Alkane solvents have been utilized in multiple reports as a substitute solvent for heavy base oils in lubricant studies. Therefore, we initially investigated the self-assembly properties of the BCPs in these solvents to gain a better understanding of the system. Three n -alkanes, n -octane, n -decane, and n -dodecane were selected to discern how alterations to the solvent choice may affect the resulting micelle properties.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding for polymer additives, the temperature dependence of the thickness and density of the adsorbed layer formed under static states has been evaluated 1 . In contrast, few operando analyses have been conducted in the shear eld 15 , and the change in the structure of the adsorbed layer formed by additives at the sliding surfaces has not been clari ed.…”
Section: Introductionmentioning
confidence: 99%
“…However, damage to the metal lm due to friction during neutron re ectometry causes operando analysis to fail. Therefore, when Armstrong et al analyzed the structure of an adsorbed layer of glycerol monooleate (GMO) under shear conditions, they set the gap between the roller and at disk to as much as 200 µm 15 . Re ectometry experiment have also been performed with a commercially available rheometer installed in a re ectometer, but the minimum gap between the cone and plate is typically on the order of 100 µm, which does not correspond to the typical oil lm thickness in tribological conditions, and the shear rate was only around 10 3 s − 1 15,18-21 .…”
Section: Introductionmentioning
confidence: 99%